(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2007)
Key words: Biochemical changes; mulberry; posdery mildew,;silkworm rearing; Phyllactinia corylea Bangladesh j. genet. biotechnol. 5 (1&2): 65068, 2004 (June & December)